Biogeography and anthropogenic impact shape the success of invasive wasps on New Zealand's offshore islands. Issue 4 (24th January 2020) - Schmack, Julia M.; Schleuning, Matthias; Ward, Darren F.; Beggs, Jacqueline R.
Abstract: Aim: The theory of island biogeography predicts that the susceptibility of an island to invasion is determined by its isolation and size. However, many island ecosystems have been intensely modified by humans. Here, we investigated the biogeographic, biotic and anthropogenic drivers of invasive social wasps on 36 offshore islands. Location: Islands off the east coast of New Zealand's North Island. Taxa: Vespula germanica (Fabricius, 1793), Vespula vulgaris (Linnaeus, 1758) and Polistes chinensis antennalis (Fabricius, 1793), Polistes humilis (Fabricius, 1781). Methods: We used GIS software for in situ randomization of plots on each island (36 islands, 409 plots) and conducted 5‐min wasp counts to estimate wasp abundance. Wasp abundance and canopy cover were recorded at each plot. Island isolation was measured using GIS software. Data on island size, human settlement and the presence of introduced rats ( Rattus spp.) were collated from the literature and island managers. The number of boat docks per island was counted from satellite images. A generalized linear mixed‐effect model (GLMM) was fitted to identify drivers of Vespula and Polistes abundance on offshore islands. Results: The abundance of Vespula was negatively correlated with island isolation and canopy cover, yet positively correlated with island size. Vespula were also more abundant on islands that have been settled by humans. The abundance of Polistes was negatively correlated with canopy cover. Finally, results did not support the notion that invasive wasps were associated with introduced rats on New Zealand's offshore islands. Conclusions: Our findings highlight the importance of biogeographic factors, such as island size and isolation, for species invasions, and suggest that intact forest cover could contribute to biotic resistance to invasive wasps in island ecosystems. Studies of invasive species should consider the joint effects of biogeographic, biotic and anthropogenic factors to best inform conservation management.